Parental Income, Socio-Cultural, and Living Environment as Factors Causing Children to Drop Out of Middle School in Rengat Barat District - Desy Haryani Z; Mahdum Mahdum; Sumarno Sumarno (Journal of Educational Sciences, 2022)
This study aims to analyze whether parental income, socio-culture, and living environment are factors that cause children to drop out of school at SMP Negeri Rengat Barat District. This study uses a quantitative approach because the research data is in the form of numbers and the analysis uses statistics to test hypotheses. The types of data used in this study are primary data and secondary data. The data analysis technique used to solve the problem in this study is a quantitative analysis technique using the KMO test (Kaiser Meyer Olkin Measure of Sampling Adequacy) and Bartleets test of sphericity. The results showed that parents' income, socio-cultural and living environment were factors that caused children to drop out of school at the State Junior High School in West Rengat District. However, the correlation value of the living environment variable is greater than the socio-cultural variables and parents' income. Thus it can be interpreted that the dominant variable affecting children dropping out of school is the environment where they live because it has the highest correlation value. Then followed by socio-cultural and finally the income of parents.